EP-434 Is Cholecystostomy the correct temporising strategy for complicated cholecystitis and how should it be utilised to meet the NICE criteria for 'early cholecystectomy'. (9th August 2022) - Ismail, Adam; Patel, Pranav H; Parmar, Chetan
Abstract: Aims: The incidence of undiagnosed gallstones is reported in up to 22% of females, with acute cholecystitis (AC) being a common emergency presentation. NICE guidance recommends index cholecystectomy for patients with proven gallstones. Emergency Laparoscopic Cholecystectomy (LC) in co-morbid patients carries a risk, with percutaneous cholecystostomy tube (PTC) insertion utilised as a temporising measure to relieve sepsis. Whilst effective at decompression, the long-term outcomes are unclear. Methods: We retrospectively reviewed all patients undergoing emergency PTC between 2019 and 2021 in our hospital. Data collection included: demographics, ASA classification, Clavien-Dindo grades, cholecystostomy complications. Results: A total 24 patients (12:12 male:female) underwent emergency PTC. Median age was 73 years (range 31–89) and median ASA grade of 3 (ASA 1 n=3, ASA 2 n=8, ASA 3 n=7, ASA 4 n=6). Median time from PTC insertion to LC was 20 weeks (range 6–73 weeks). Morbidity post PTC according to Clavien-Dindo grades were: 4 with grade 3 (16.7%), 5 with grade 4 (8.3%) and 5 with grade 5 (20.8%). 8 patients (33.3%) re-presented with further cholecystitis. 4 (16.7%) patients had completion LC, without complication. Conclusions: Our findings highlight significant morbidity and mortality in this high-risk cohort secondary to complicated AC. 20 patients (83.3%) did not undergo a completion cholecystectomy, despite 18 being ASA 1–3. We suggest a judicious use of PTC and a greater focus on index multi-disciplinary surgical fitness assessment in order to optimise a patient for acute LC. This strategy is key to enable full adoption of AUGIS guidance for performing LC within 72 hours.